Perlindungan Sumber Daya Alam dalam Islam - Efendi Efendi (Universitas Syiah Kuala, 2011)
ABSTRACT: Islam views human as protectors and keepers the resources of the earth but there is the fact that human is a destroyer of such resource. Based o such reason, it is interesting to explore the protection concept especially regarding water, land, anima and plants is Islam. The concept in Islam is based on the view that the protection for the universe; therefore, keeping and protection the natural resource is a total part of human good deed. Natural Source Protection in Islam